Implementasi Pembelajaran Pendidikan Kewarganegaraan Berbasis SDGs dalam Membentuk Green Civic Behavior Mahasiswa - Desvi Emti; Ikhwani Ratna (Yayasan Almanar Pujud, 2026)
This study aims to analyze the implementation of SDGs-based Civic Education learning in shaping students' green civic behavior. This study uses a qualitative approach with a case study method. Research data were obtained through learning observations, interviews with Civic Education lecturers, students, and analysis of learning documents. Data analysis used the interactive model of Miles, Huberman, and Saldana which includes data condensation, data presentation, and drawing conclusions. The results show that the implementation of SDGs-based Civic Education learning is carried out through the integration of sustainability issues in learning materials, the use of problem-based learning strategies, discussions, and environmental projects. This learning is able to improve students' understanding of the relationship between citizenship and environmental sustainability. The development of students' green civic behavior is demonstrated through increased concern for the environment, awareness of reducing consumptive behavior, waste management, and participation in environmental activities. This study shows that the integration of SDGs in Civic Education learning can be a strategic approach in shaping citizens who have ecological awareness and are responsible for sustainability.